An Investigation of Approaches and Strategies in Teaching Indonesian Writing: Voices of Indonesian Language Teachers - Nuswantara, Kartika; Tantri, Niki Raga; Rohmah, Zuliati; Al-Mustofa, Muhammad Ubaidillah; Rintaningrum, Ratna (JOALL (Journal of Applied Linguistics and Literature), 2024)
This study aimed to gather information about the approaches and strategies used by Indonesian language teachers in teaching writing lessons in Indonesian language classes in response to the previous studies identifying junior high school students’ challenges in Indonesian language writing. A survey was done using an online questionnaire distributed to 166 teachers from various schools in the country. However, only 126 were taken, as the rest admitted that they did not teach Indonesian language writing in their classes. The questionnaire was adopted from Self-Assessment of Writing Strategies by Marquette University and was validated to serve valid and reliable data. The data were analyzed using descriptive statistics, and teachers’ proficiency in coping with various approaches to teaching the language and their keen strategies to help students in the writing classes were found. The findings suggested that despite teachers' proficiency in many approaches to teaching, students still encountered challenges in multiple aspects of writing. Therefore, there was a need for continuous improvement in curriculum design and to assist students through corrective feedback to help them cope with their writing problems. In summary, the study emphasized the importance of ongoing research, professional development, and improved writing instruction.